Serum Fetuin-A Level in Patients With Ankylosing Spondylitis and its Relationship With Clinical Parameters - Ferhat GÖKMEN,; Ayla AKBAL,; Fahri GÜNEŞ,; Hakan TÜRKÖN,; Ahmet VURAL,; Emine BİNNETOĞLU,; Erkam KÖMÜRCÜ,; Hacer ŞEN Mehmet AŞIK,; Erdem AKBAL, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the association of serum fetuin-A levels with disease activation and clinical parameters in ankylosing spondylitis (AS) patients. Patients and methods: Forty-seven AS patients (30 males, 17 females; mean age 39.7±11.1 years; range 20 to 69 years) and 30 healthy controls (14 males, 16 females; mean age 42.0±11.5 years; range 19 to 63 years) were included in the study. Erythrocyte sedimentation rate, C-reactive protein, Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Functional Index, Bath Ankylosing Spondylitis Radiology Index, and Bath Ankylosing Spondylitis Metrology Index were used in the assessment of AS. Serum fetuin-A levels were measured using ELISA. Results: Mean serum fetuin-A values in AS patients (984±203 ng/mL) were significantly lower compared to controls (1156±218 ng/mL) (p=0.001). While a statistically significant negative correlation was detected in AS patients between fetuin-A values and C-reactive protein (p=0.009, r=-0.377), no significant correlation was detected between erythrocyte sedimentation rate, Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Metrology Index, Bath Ankylosing Spondylitis Functional Index or Bath Ankylosing Spondylitis Radiology Index parameters and fetuin-A. Conclusion: Serum fetuin-A levels in AS patients were lower than the control group. However, further research is required to establish the role of serum fetuin-A levels as a surrogate marker of disease activity.